Comparison of executive functions and functional outcome between older patients with traumatic brain injury and normal older controls. Issue 5 (3rd September 2022) - de Guise, Elaine; Degré, Catherine; Beaujean, Océane; Julien, Jessica; Lague-Beauvais, Maude; Dagher, Jehane; Marcoux, Judith
Abstract: Context: The aim of this preliminary study was to assess the impact of traumatic brain injury (TBI) in older age on executive functioning and on their functional outcome. We also aimed to explore the influence of cognitive reserve (CR) and estimated premorbid cognitive functioning (EPCF) on these components. Methods: A neuropsychological and functional assessment that included tests measuring Inhibition, Updating and Shifting, and functional outcome was administered to 29 patients who sustained a mild or moderate TBI in older age and a group of 24 healthy older participants. CR (level of education) and EPCF variables collected in the TBI group were associated with executive function performance and functional outcome. Results: Patients with TBI obtained significantly worse performances on the spatial working memory (WM) task-reverse condition, and on the completion time of the Trails A and B than the control group. The TBI group also obtained worse functional outcome scores. A higher level of education was associated with better WM performance, and higher estimated premorbid cognitive functioning was associated with better functional outcome post TBI. Conclusions: Further studies with a larger sample should be conducted to better understand the profile and determinants of recovery from TBI in the elderly.